Exact null internal controllability for the heat equation on unbounded convex domains∗. (6th February 2014) - Barbu, Viorel
<x content-type="archive" xml:space="preserve">Abstract</x> The liner parabolic equation <alternatives> <![CDATA[yt-12 y+F· a y=1__0u]]> <inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2zjwwzqh" xmlns:xlink="http://www.w3.org/1999/xlink" />∂y∂t−12 Δy+F·∇y=1𝒪0u</alternatives> with Neumann boundary condition on a convex open domain 𝒪 ⊂ ℝd with smooth boundary is exactly null controllable on each finite interval if 𝒪0 is an open subset of 𝒪 which contains a suitable neighbourhood of the recession cone of <alternatives> <![CDATA[]]> <inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2zjwwzsm" xmlns:xlink="http://www.w3.org/1999/xlink" />𝒪</alternatives>. Here, F : ℝd → ℝd is a bounded, C1-continuous function, and F = ∇g, where g is convex and coercive.